Didactic analysis of the results of solving tasks of school-scale mathematical competitions for fourth formers - Kiseliova, Danutė; Kiseliovas, Arkadijus (Lietuvos matematikos rinkinys, 2004)
The research has randomly selected 2581 from more than 5000 competition works by fourth formers from Lithuania’s all cities and districts. The central and, probably, the most important aim and task of such competitions includes development of primary formers’ interest in mathematics, development and improving of their mathematical achievements, knowledge, development of creativity, logical and critical thinking. The relation between pupils’ mathematical achievements in schools and their competition results partially proves the hypothesis that well-studying pupils refer to the rules, strict algorithms, in turn, they trust in their capacities, and thus pay less attention to the tasks, the relations of which require involvement of creativity, as they consider them to be easy. Consequently, pupils who knew the rules not so well, showed better results in namely those problems, which required creativity.